Factors influencing the satisfaction among volunteers in volunteering at Matang Wildlife Centre, Sarawak / Jessie Anak Rudi ... [et al.] - Rudi, Jessie; Daniel, Natasha Bija; Gatu, Alvin; Mohamad Musa, Nurafiqah; Mohd Zaidi, Nur Murniza (Universiti Teknologi MARA, Sabah, 2023)
Volunteering activities can bring great impacts and meaningful experiences for volunteers. Various factors influence volunteers to participate in volunteer activities. This study was conducted to examine the factors influencing the satisfaction among volunteers in volunteering activities at Matang Wildlife Centre, Sarawak. The study focused on the relationship of certain variables, including personal value, behavioural intention, social needs, and volunteers’ satisfaction. Specifically, i) to determine the correlation between personal value and volunteers’ satisfaction in volunteering activities at Matang Wildlife Centre, Sarawak. ii) to identify the correlation between behavioural intention and volunteers’ satisfaction in volunteering activities at Matang Wildlife Centre, Sarawak. iii) to investigate the correlation between social needs and volunteers’ satisfaction in volunteering activities at Matang Wildlife Centre, Sarawak. Using an online questionnaire via Google Forms, data were collected from 178 volunteers. The survey questionnaire was adapted from previous studies. Some modifications were made to suit the context of the present study. Based on the results, the study shows that motivational factors like personal values, behavioural, and social needs have a significant correlation with the volunteers’ satisfaction at Matang Wildlife Centre.